Anti-Inflammatory Targets for the Treatment of Reperfusion Injury in Stroke - Mizuma, Atsushi; Yenari, Midori A. (Frontiers in Neurology, 2017)
While the mainstay of acute stroke treatment include revascularization via rt-PA or mechanical thrombectomy, only a minority of stroke patients are eligible for treatment, as delayed treatment can lead to worsened outcome. This worsened outcome at the experimental level has been attributed to an entity known as reperfusion injury (R/I). R/I is thought to occur when revascularization occurs after critical brain and vascular injury has occurred, so that when oxygenated blood is restored, ischemic damage is increased, rather than decreased. R/I can increase lesion size, but also worsen blood barrier breakdown and lead to brain edema and hemorrhage. A major mechanism underlying R/I is that of post stroke inflammation. The post stroke immune response consists of the aberrant activation of glial cell, infiltration of peripheral leukocytes, and the release of damage-associated molecular pattern (DAMP) molecules elaborated by ischemic cells of the brain. Inflammatory mediators involved in this response include cytokines, chemokines, adhesion molecules, and several immune molecule effectors such as matrix metalloproteinases-9, inducible nitric oxide synthase, NO, and reactive oxygen species. Several experimental studies over the years have characterized these molecules and have shown that their inhibition improves neurological outcome. Yet, numerous clinical studies failed to demonstrate any positive outcomes in stroke patients. However, many of these clinical trials were carried out before the routine use of revascularization therapies. In this review, we cover mechanisms of inflammation involved in reperfusion injury, therapeutic targets, and relevant experimental and clinical studies which might stimulate renewed interest in designing clinical trials to specifically target R/I. We propose that by targeting anti-inflammatory targets in R/I, that it may be possible to further improve outcomes from pharmacological thrombolysis or mechanical thrombectomy, or, by combining anti-inflammatory treatments with revascularizing therapies, prolong the temporal therapeutic window for such treatments.